15th century Renaissance in full bloom - Hribar, Mariano Nicora (Masterpieces of Italian Art, 1990)
Presents key masterpieces of artists during the flowering of the Renaissace in 15th century Italy like Botticelli, Angelico, Codussi, Lambardo, Bellinis Carpaccio Andrea del Castagno, etc.